Do Antibodies to Malaria Surface Antigens Play a Role in Protecting Mothers From Maternal Anemia? - Wiebe, Madeleine C.; Yanow, Stephanie K. (Frontiers in Immunology, 2020)
Pregnancy-associated malaria (PAM) caused by Plasmodium falciparum can result in detrimental outcomes for both mother and infant, including low infant birth weight, preterm birth, maternal anemia, spontaneous abortion, and maternal and/or infant mortality. Maternal anemia is a particularly complex outcome, as the body must both maintain erythropoiesis and tolerance of the growing fetus, while directing a Th1 response against the parasite. Underlying the pathogenesis of PAM is the expression of variable surface antigens (VSAPAM) on the surface of infected red blood cells (iRBC) that mediate sequestration of the iRBC in the placenta. Naturally acquired antibodies to VSAPAM can block sequestration and activate opsonic phagocytosis, both associated with improved pregnancy outcomes. In this review, we ask whether VSAPAM antibodies can also protect mothers against malarial anemia. Studies were identified where VSAPAM antibody titres and/or function were associated with higher maternal hemoglobin levels, thus supporting additional protective mechanisms for these antibodies against PAM. Yet, these associations were not widely observed, and many studies reported no association between protection from maternal anemia and VSAPAM antibodies. We discuss the epidemiological, biological and technical factors that may explain some of the variability among these studies. We appraise the current evidence of these complex interactions between PAM-specific immunity and maternal anemia, propose potential mechanisms, and discuss knowledge gaps.